New strategies to inhabit the rural environment: Intervention in the Alqueria de Tablate (Granada, Spain) - Jiménez-Trigo, Elvira; García Moreno, Alberto E. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The alqueria of Tablate is a unique uninhabited architectural object because it is a Nasrid vestige with enormous heritage value. The main objective of the research and intervention on this enclave is the definition of a proposal that involves an innovation in the rural way of living. The resulting system is an example of how to bring industrialization closer to tradition through the abstraction of the bases of Andalusian popular architecture. A reflection on how to incorporate concepts such as reversibility, virtuality, or agricultural activity to contemporary architecture.